The elements of user experience : user-centered design for the Web and beyond - Garrett, Jesse James (Berkeley, CA : New Riders, 2011)
Provides an overview of the complexities of interactive Web design for non-designers, explaining the processes, methods, and vocabulary of user experience design.
Chapter 1. User Experience and Why It Matters -- Chapter 2. Meet the Elements -- Chapter 3. The Strategy Plane Product Objectives and User Needs -- Chapter 4. The Scope Plane Functional Specifications and Content Requirements -- Chapter 5. The Structure Plane Interaction Design and Information Architecture -- Chapter 6. The Skeleton Plane Interface Design, Navigation Design, and Information Design -- Chapter 7. The Surface Plane Sensory Design -- Chapter 8. The Elements Applied -- Index.
Includes index.
Includes bibliographical references and index.
Keywords: Web sites -- Design; Human-computer interaction; Web sites -- Design; Human-computer interaction